Physiological quality of soybean seeds artificially cooled and stored in different packages - Zirvaldo Z. Virgolino; Osvaldo Resende; Douglas N. Gonçalves; Kaique A. F. Marçal; Juliana de F. Sales (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The aeration of seeds with artificially cooled air and their storage in big-bag packages aim to lengthen the shelf life while maintaining the quality. Thus, the objective was to study the effects of cooling before storage on germination and vigor of soybean seeds stored in trifoliate kraft paper bag and big bag in non-air-conditioned environment. Seeds of soybean cultivar NA 7337 RR were mechanically harvested in March 2013, holding an average moisture content of 18% w.b. In June, 16,000 kg of seeds were processed and cooled to 18 °C. Equal amount of non-cooled seeds was used as a control. Equally divided in kraft paper and in big bags, and combining cooling and packaging, the seeds were stored for three months and analyzed for moisture content, germination and vigor. Cooling to room temperature and different packaging types had similar effects on seed quality. Big bags packing showed better efficiency in retaining the moisture content of cooled seeds. No direct effects of cooling could be identified prior to storage on the germination and vigor of soybean seeds.